Hydrogeochemical controls on mobilization of arsenic in groundwater of a part of Brahmaputra river floodplain, India - Mahanta, C.; Enmark, G.; Nordborg, D.; Sracek, O.; Nath, B.; Nickson, R.; Herbert, R.; Jacks, G.; Mukherjee, Abhijit; Ramanathan, A.; Choudhury, R.; Bhattacharya, P. (2015)
© 2015 The Authors. Study region: Arsenic enriched groundwater regime within low-industrialized Brahmaputra floodplains in Assam, NE India. Study focus: We examined the origin, distribution and processes of As release by investigating the salient groundwater chemistry and subsurface sedimentological characteristics. Besides collection of groundwater samples from domestic and public water supply wells, sediment samples from boreholes were investigated for textural and colour linkages. New hydrological insights for the region: Arsenic concentrations above the WHO guideline value of 10 µg/L were present in 33 wells and above the previous Indian national drinking standard of 50. µg/L were present in 15 wells. The green-olive colour sediments were more likely to yield As-enriched groundwater. The supersaturation of groundwater with respect to Fe(II) minerals, such as siderite and vivianite, explained the poor correlation between dissolved As and Fe. The result reinforced the phenomenon of reductive dissolution of Fe(III) oxyhydroxides releasing As to groundwater. This study throws light on the processes and mechanisms involved with As release in groundwater. The homogenous floodplain terrain makes the hydrological As imprint unambiguous and the hydrogeological signatures untarnished. Considering the absence of anthropogenic sources in the study area, the conclusions on the nature and causes for As release to groundwater looked dependable although the final contamination at specific subsurface sites would be influenced by advection-dispersion of groundwater flow accompanied by retardation, ion exchange, surface complexation and possible biodegradation.